Heterogeneous Labor Market Adjustments to Offshoring in European Regions - Ulrich Theodor Zierahn; Melanie Arntz; Jan Hogrefe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Offshoring is often found to be associated with an increase of wage inequality between low- and high-skilled. This is interpreted as a relative decrease of low-skilled labor demand. However, the effect of offshoring on relative labor demand is ambiguous, since low-skilled workers may benefit from productivity effects of offshoring. Moreover, whether offshoring affects wages or (un-)employment depends on the flexibility of the labor market. The labor market responses to offshoring could thus be very heterogeneous across regional labor markets. We estimate the effects of offshoring to Eastern Europe and China on labor markets in Western European regions and find that (1) offshoring has led to a decrease of low-skilled wages. (2) In low-patent regions the effects are more pronounced and positive effects on unemployment emerge. This indicates that productivity effects could play a role in compensating the labor market effects of offshoring. (3) There is some evidence that the labor market effects depend on the types of enterprise functions which are offshored. (4) The effects on unemployment are weaker in regions which spend more money on active labor market policy.
Keywords: F66; J23; R23; 330